1999
DOI: 10.1080/01904169909365713
|View full text |Cite
|
Sign up to set email alerts
|

Mineral composition of leaves and flower buds in fruiting and non‐fruiting pistachio trees

Abstract: The effect of fruiting on mineral composition of leaves and flower buds in pistachio (Pistachia vera L., cv. Aegenes) was studied in two experimental years (1990 and 1992). Nutrient concentrations were measured in leaves and flower buds on fruiting and non-fruiting pistachio trees at two week intervals from leaf emergence until the flower bud abscission of fruiting trees was completed. The results showed that the presence of fruit significantly increased the leaf concentrations of magnesium (Mg), calcium (Ca),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 12 publications
3
8
1
Order By: Relevance
“…Leaf K concentration in the OFF-year was higher than that in the ON-year in trees of different ages and in all the regions. This is in line with the findings of Vemmos (1999). Also, mature heavy bearing pistachio trees have been shown to take up approximately 224 kg ha − 1 of K during the ON-year and 112 kg ha − 1 during the OFF-year.…”
Section: Leaf K Concentrationsupporting
confidence: 84%
“…Leaf K concentration in the OFF-year was higher than that in the ON-year in trees of different ages and in all the regions. This is in line with the findings of Vemmos (1999). Also, mature heavy bearing pistachio trees have been shown to take up approximately 224 kg ha − 1 of K during the ON-year and 112 kg ha − 1 during the OFF-year.…”
Section: Leaf K Concentrationsupporting
confidence: 84%
“…The results presented here suggest that levels of N were lower in all tree parts, except fruits of ON trees and buds of OFF trees by 70 DAFB. These dates did not agree with the report of Vemmos (1999), who found that the presence of fruits decreased leaf and flower bud N content after the commencement of seed growth and high rates of bud abscission. In contrast, our results were in agreement with those reported by Uriu and Crane (1977) and Durzan (1996), who found that flower buds and leaves on bearing trees had lower N concentrations than those on nonbearing trees.…”
Section: Minerals In Pistachio Trees 253contrasting
confidence: 71%
“…In buds and leaves of ON trees, lower K concentration, especially in the period of nut filling (from 100 DAFB), may have been due to fruit requirements for more, K than other nutrients and the possible movement of K from flower buds and leaves to fruits. This hypothesis is supported by results of Brown, Weinbaum, and Picctioni (1995) and Vemmos (1999), who found that fruits and abscised leaves of fruiting trees removed 131 Kg K but only 18 kg P ha 21 annually. Rosecrance, Weinbaum, and Brown (1996) also showed that ON trees accumulated K in fruit, whereas OFF trees stored K in perennial tissues during the nut-fill period.…”
Section: Minerals In Pistachio Trees 253supporting
confidence: 58%
“…Clusters of "Pontikis" cultivar exhibited almost 71€3 nuts each, while those of "Aegenes" exhibited almost 161€15 nuts. Flower bud abscission in "Aegenes" is usually completed by mid-August (Vemmos 1999b), while in the present case this period was prolonged until the end of September. This is clearly the result of the late flowering and maturation of "Pontikis" cultivar along with the low number of nuts per cluster, which according to Porlingis (1974) and Crane and Nelson (1972) influences the flower bud abscission rate.…”
Section: Pattern Of Flower Bud Abscissionmentioning
confidence: 86%
“…It has been suggested that the competition for metabolites and nutrients between the ovary and the flower buds is responsible for the abscission of the latter (Vemmos et al 1994;Brown et al 1995;Rosecrance et al 1996;Nzima et al 1997, 1999, Vemmos 1999a. However, other experiments have indicated that unbalanced nutrition was not the primary cause of bud abscission, and attention should be given to the involvement of plant growth regulators (Porlingis 1974;Crane and Iwakiri 1987;Stevenson and Shakel 1998;Vemmos 1999b). Neither abscisic acid nor gibberellin-like compounds in developing fruit and flower buds showed any relationship with the bud abscission (Takeda and Crane 1980;Lin et al 1984;Crane and Iwakiri 1987), while auxins could be a possible messenger of bud abscission, but not the cause (Pontikis 1990).…”
Section: Introductionmentioning
confidence: 95%